Brazilian Consensus for the Treatment of Multiple Sclerosis: Brazilian Academy of Neurology and Brazilian Committee on Treatment and Research in Multiple Sclerosis - Vanessa Daccach Marques; Giordani Rodrigues dos Passos; Maria Fernanda Mendes; Dagoberto Callegaro; Marco Aurélio Lana-Peixoto; Elizabeth Regina Comini-Frota; Cláudia Cristina Ferreira Vasconcelos; Douglas Kazutoshi Sato; Maria Lúcia Brito Ferreira; Mônica Koncke Fiuza Parolin; Alfredo Damasceno; Anderson Kuntz Grzesiuk; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT The expanding therapeutic arsenal in multiple sclerosis (MS) has allowed for more effective and personalized treatment, but the choice and management of disease-modifying therapies (DMTs) is becoming increasingly complex. In this context, experts from the Brazilian Committee on Treatment and Research in Multiple Sclerosis and the Neuroimmunology Scientific Department of the Brazilian Academy of Neurology have convened to establish this Brazilian Consensus for the Treatment of MS, based on their understanding that neurologists should be able to prescribe MS DMTs according to what is better for each patient, based on up-to-date evidence and practice. We herein propose practical recommendations for the treatment of MS, with the main focus on the choice and management of DMTs, as well as present a review of the scientific rationale supporting therapeutic strategies in MS.